Quality, innovations and Sustainable Development Goals: challenges for higher education in Latin America (Dissertare, 2022)
University sectors have accepted the high education quality and its evaluation as a tool to keep and to strengthen institutional pertinence and reliability. A new challenge that is put to higher Education Institutions (HEI) is the need to develop transversal competences and innovations in teaching-learning processes, to achieve, through the training of graduates of HEI, sustainability and achievement of the purposes of the Sustainable Development Goals (SDG). In view of the above, this work draw as objective to carry out a bibliographic review related to the quality of higher education in Latin America and the new educational proposals for the scope of the SDGs, as an aspect that contributes to the strengthening of such a quality. The need for a greater authentic commitment of the HEI to accomplish the objectives of SDG was recognized, as well as, that these should make a better effort to achieve Sustainable Development (SD). Furthermore, some innovative alternatives were put forward, like some methods to facilitate teaching-learning to allow awareness of the HEI’s graduates with regard to that end, using didactic strategies, like electronic learning, through the use of cellular phones or other electronic devices; learning-service, graphic novels and gamification.
Keywords: sustainability; higher education; Sustainable Development Goals; educational innovations; quality of education